PERSAMAAN PERTAMA MAXWELL RELATIVISTIK BINTANG NEUTRON YANG BEROTASI CEPAT BINTANG NEUTRON YANG BEROTASI CEPAT DIUKUR OLEH PENGAMAT ZAMO (ZERO ANGULAR MOMENTUM OBSERVERS) - Atsnaita Yasrina (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2016)
Neutron star is an object in Milky Way that is studied relativistically using general relativity theory. One of the fields of study of the Neutron Star is the reduction of its magnetic field. Therefore, the equation of magnetic field dynamic is needed to show the reduction of magnetic field in the Neutron Star. The equation formula of magnetic field dynamic can be drawn from the first equation of Maxwell’s relativistic. If the Neutron Star being studied is rotating, it is important to use ZAMO (Zero Angular Momentum Observers) base. The first Maxwell’s relativistic on the Neutron Star rotating quickly has been formulated and was measured by ZAMO observer. The equation drawn was only limited on deferential equation in radial, polar, and azimuth components